The professional learning of the adult-child interaction: a multi-contextual study - Novo, Rosa (2012)
The aim of this poster is to understand the educational interaction of trainee-educators with reference to the pedagogical option adopted in the supervising context An issue emerging from some research studies stresses the understanding that interaction competences depend on long, subsequent processes of reflected professional learning (Oiiveira-Formosinho, 2002, 2003; Pascal and Bertram, 2003). In this study, the ecological, socio-constructivist model of supervision of final teaching practice (Oiiveira-Formosinho, 2002) becomes of fundamental relevance because of its assumed need to consider child pedagogy as substantive to the construction of a new vision on practical training and on a new meaning of pedagogical supervision considered as adjectival (Oiiveira-Formosinho, 2005). Using the Adult Engagement Scale (Laevers, 1994 ), our research followed an approach descriptive and interpretative in nature and the data collection process was based on the. analysis of video-recordings, field notes, training reflective portfolio and interviews with the trainees. Given the characteristics of the study, informed consent of the subjects was obtained and the secrecy of their identity and the identification of places are safe. Among the conclusions draw from data, the interactivity between the learning's of pre-school teacher trainees and the pedagogical grammar adopted in the training context. lt should furthermore be emphasized that not all practical training is a sufficient guarantee to a participative pedagogy. Results show the absolute need for thinking the institutional importance given to the role of the supervisor over again and, as a consequence, to the of continuous training offered.